FREE RADICAL SCAVENGING ACTIVITY OF TWO MEDICINAL PLANTS USED BY DIABETIC PATIENTS IN BOTSWANA - Motlhanka, D.; Motlhanka, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Water extracts of Myrnthamnus flabellifolius (shoot) and Ozoroa paniculosa (roots, stem, leaves) and their combinations called “Dankatso” (equal proportion of the above plant extracts) are being used extensively in eastern Botswana traditional medicine. These plants have reputable use as antidiabetic preparations. M. flabellifolius is used to alleviate symptoms of diabetes mellitus, stroke and hypertension. O. paniculosa is used to alleviate menstrual pain and in asthma (Motlhanka, 2008). The study is part of an ongoing project to search for novel drugs from vast array of medicinal plants from Botswana, which have not been studied extensively (Motlhanka et al., 2005), The antioxidant capacity of the extracts together with their combinations was assessed spectrophotometrically using DPPH free radical scavenging assay. At 25 Âµg/ml the scavenging power of the extracts were as follows: M. flabellifolius alone (66%); O. paniculosa root alone (49%); O. paniculosa stem alone (81%); O. paniculosa leaf alone (79%). At the same concentration (25 Âµg/ml), combinations: [M. flabellifolius+O. paniculosa root] (85%); [M. flabelllifolius + O. paniculosa stem] (91%); [M. flabellifolius + O. paniculosa leaf] (91%). At 100 Âµg/ml and above there were no significant differences between scavenging potencies for individual extracts and their combinations (“Dankatso”). The scavenging potencies were in magnitudes of 90-91% for individual extracts and their combinations. This study suggests that the presence of antioxidant compounds in water extracts of the studied plants may be responsible for their anti-diabetic properties as advocated in traditional medicine. Acknowledgements: Traditional healers for supplying the plants. References: Motlhanka D.M et al. (2005) J. of Pharm. & Pharmacol. Vol: 57 S-7.Motlhanka, D.M (2008) Pakistan J of Biol. Sci. Vol:11 (5) 805-808